Labor Shortage in Seven Central and Eastern European Countries in Transition: Before and During COVID 19 - József Poór; Imrich Antalik; Allen D. Engle; Timea Juhász; Vilmanté Kumpikaitė Valiūnienė; Zivile Stankeviciute; Ádám Kovács; Péter Karácsony; Kinga Kerekes; Monica Zaharie; et al. (Journal of Corporate Governance Research, 2024)
Based on the responses of the surveyed companies and institutions, we analyzed what government measures help to solve the problems and tensions in the labor market. By our empirical research we aimed to look for the main triggers and the typical means of labor shortage and labor retention. We also examined what efficiency improvement plans and robotization programs are either planned or have already been implemented by the responding organizations. The study reflects the empirical results conducted in 2019 in seven countries in the region. One of the key issues in these countries during the period considered is the dramatic increase in labor shortages, which has been influenced by a variety of factors, namely outbound labor migration after the change of regime, unfavorable demographic factors, national and regional economic downturns as well as persistent wage differences within the EU. Wages and work-life balance are the two important factors that have a significant impact on labor mobility and fluctuation for both skilled and less skilled labor. Responses indicated a variety of reasons for labor shortages, different reasons in different countries. The research also provided an indication that robotization alone is not a solution to address labor shortages.